Quality Control Analysis on Nylon Monofilament Net Production Process Using the Seven Tools Method and FMEA at PT ARIDA - Muhamad Iskhaq; Hidayat Hidayat; Akhmad Wasiur Rizqi (Jurnal Serambi Engineering, 2023)
PT. ARIDA is a company engaged in the fishing net production manufacturing industry. This company experienced difficulties in controlling the quality of the nylon monofilament net production process. Quality control is carried out to reduce the occurrence of defects. The author uses the Seven Tools and FMEA methods to analyze the level of defects and look for factors that cause defects that occur. The author uses the Seven Tools and FMEA methods to analyze the level of defects and look for factors that cause defects that occur. The research results show that the defect rate that occurs is 8.97%, this shows that the production process is not under control. Proposed control of potential causes based on RPN values so that companies can prioritize improvements to potential causes that occur.